2014
DOI: 10.1007/s00417-014-2734-z
|View full text |Cite
|
Sign up to set email alerts
|

ILM peeling technique influences the degree of a dissociated optic nerve fibre layer appearance after macular hole surgery

Abstract: ILM peeling technique and possibly other surgeon-specific factors appear to influence the extent of DONFL observed after ILM peeling macular hole surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 25 publications
(36 reference statements)
0
22
1
1
Order By: Relevance
“…In regards to the role of specific surgical instruments architectural alterations, Steel et al 20 compared the forcepsonly group (41 eyes) versus DDMS-only group (16 eyes) and concluded that the DDMS was associated with increased postoperative retinal changes. Importantly, no iOCT data were available in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In regards to the role of specific surgical instruments architectural alterations, Steel et al 20 compared the forcepsonly group (41 eyes) versus DDMS-only group (16 eyes) and concluded that the DDMS was associated with increased postoperative retinal changes. Importantly, no iOCT data were available in this study.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 We performed ILM peeling in RRD patients and noted that forceps might press the attached retina against the choroid and sclera without macular detachment, whereas the forceps might not press the free-floating retina with macular detachment. Threedimensional OCT clearly visualized time-dependent retinal changes in the wide-field comprehensive topography, which were sometimes difficult to observe with the conventional cross-sectional OCT. To test the mechanical insult that causes the retinal structural changes after ILM peeling, we hypothesized that ILM forceps may induce the changes in part by pressing and grasping the ILM and inner structures of the retina.…”
mentioning
confidence: 99%
“…Subtle superficial retinal hemorrhages are reported to be encountered in 66% to 75% of patients as ILM peeled with either a diamond-dusted membrane scraper or forceps. 12 These hemorrhages usually are self-limited, which do not appear to have long-term implications. 13 There have been rare reports of more serious issues during ILM peeling, such as significant intraoperative bleeding from small retinal vessel damage that may result in postoperative hyphema with high intraocular pressure.…”
Section: Discussionmentioning
confidence: 99%